2020
DOI: 10.5194/wes-2020-79
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A surrogate model approach for associating wind farm load variations with turbine failures

Abstract: Abstract. In order to ensure structural reliability, wind turbine design is typically based on the assumption of gradual degradation of material properties (fatigue loading). However, the relation between the wake-induced load exposure of turbines and the reliability of their major components has not been sufficiently well defined and demonstrated. This study suggests a methodology that makes it possible to correlate loads with reliability of turbines in wind farms in a computationally efficient way by combini… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Neural network models have been used to build efficient surrogate models based on measured operational data or high-fidelity simulation data. These surrogate models are capable of estimating wake-induced effects on wind turbine power [1,2,3], loads [4,5], damage and failures [6]. These surrogate models, among other applications, enable efficient optimization of wind farm layout and control strategy [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…Neural network models have been used to build efficient surrogate models based on measured operational data or high-fidelity simulation data. These surrogate models are capable of estimating wake-induced effects on wind turbine power [1,2,3], loads [4,5], damage and failures [6]. These surrogate models, among other applications, enable efficient optimization of wind farm layout and control strategy [5,7].…”
Section: Introductionmentioning
confidence: 99%
“…Ashuri et al (2016), Murcia et al (2018), and Schröder et al (2020a) used surrogate models for uncertainty propagation through the wind turbine models. More recently, the surrogate models have been used for the wind turbines' reliability assessments (Slot et al, 2020;Schröder et al, 2020b). Also, Wang et al (2020) and Barlas et al (2021) showed the application of the surrogate model in wind turbine optimization.…”
Section: Introductionmentioning
confidence: 99%
“…Initiating from a physics-based approach, research in [12] and in similar works [41,37] exploits a surrogate approach, relying on Polynomial Chaos Expansions (PCE) and Artificial Neural networks (ANN), trained on pre-simulated load scenarios, to predict the fatigue load variation on WTs for a wind farm with arbitrary layout under wake effects. ANNs are shown to outperform PCE in terms of prediction accuracy and computational speed [40], albeit being prone to overfitting, while further require significantly more data for achieving acceptable performance. Both methods allow for obtaining analytical derivatives, which is a useful trait in optimization and sensitivity analysis.…”
Section: Introductionmentioning
confidence: 99%